Probabilistic seismic hazard analysis and determination of uniform hazard spectrum of Bushehr province assuming linear source model - Amin Keshavarz (Iranian Society of Structrual Engineering (ISSE), 2018)
Due to the high complexity in the mechanism of earthquakes occurrence, it is not possible to predict it accurately at a given site. Experiences and scientific findings indicate that using the statistical and probabilistic techniques entitled seismic hazard analysis, the safety of the structures can be desirably assessed. This study evaluates the seismic hazard of Bushehr province using the probabilistic and in some cases the deterministic approaches. To assess the seismic hazard, an area of 150 km around Bushehr province has been considered. Seismic linear sources have been prepared using the available maps. Historical and instrumental earthquake catalogue has been provided using the published catalogues. Foreshocks and aftershocks have been removed from the catalogue by applying the Gardner and Knopoff algorithm. Then, by employing the Keijko and Gutenberg-Richter methods, suitable seismicity parameters have been calculated. Finally, according to the seismic power of each fault, the mentioned parameters have been assigned to the faults. Seismic hazard analysis has been performed using the desirable ground motion prediction equations. Results have been presented as the deterministic and probabilistic acceleration response spectra for important cities. The probabilistic seismic hazard zonation maps have been provided for the return periods of 75, 475 and 2475 years.